Methodological Approaches to Managing a Tourism Company’s Strategic Development - NOVAK, Liliya Vasilyevna; KOZHINA, Veronika Olegovna; MARKOVA, Olga Vladimirovna; SHADSKAYA, Irina Gennadievna; FEDULIN, Aleksandr Alekseevich (Journal of Environmental Management and Tourism, 2019)
This paper is devoted to the development of approaches to managing a tourism company’s strategic development. It is established that in present-day conditions the most crucial stage in strategic management in a tourism company is strategic analysis, which helps gather, evaluate, and systematize information that is needed to make strategic decisions. The availability of internal resources and external potential in a tourism company is the subject of strategic management, aimed at transforming them into real factors for success. The authors establish that a tourism company’s focus on resolving issues of long-term planning and sustainable development may require employing a set of methods, methodologies, models, and tools for strategic management and utilizing the market- and resource-based approaches. It is proven that the use of concepts which underpin these approaches could help make quality use of the tools for strategic management in present-day conditions.